The advantages of NK cell vaccines in solid carcinoma clinical trials: conducted by various biology strategy and technology - Hu, Yizhe; Leng, Limei; Li, Bing; Qiao, Qiang (Frontiers in Medicine, 2025)
This review systematically discusses the latest clinical progress and challenges of natural killer (NK) cell vaccines in the treatment of solid tumors. By searching databases such as ClinicalTrials.gov and PubMed (2019–2025), we focused on preclinical studies and Phase I/II/III registration trials in the past 2–3 years to dissect the mechanism of action and efficacy data of different vaccine platforms. The study illustrated: Dendritic cell-based vaccine platforms (e.g., ilixadencel), cytokine-based vaccine platforms (e.g., ALT-803), NK receptor agonist antibodies (e.g., AFM24) and mRNA/LNP-based vaccine platforms (e.g., BNT116) It has shown early efficacy in solid tumors such as non-small cell lung cancer, triple-negative breast cancer, and glioblastoma (with partial ORR of 30–50% and DCR of 80–100%), and the safety is comparatively manageable (the incidence of grade ≥3 adverse events is less compared to T-cell therapy). However, complex manufacturing procedures, inhibition of the tumor microenvironment, and low targeted delivery efficiency remain the main obstacles to transformation. In the future, combinatorial regimens (e.g., sequential application of PD-1 inhibitors) need to be optimized, an iPSC-NK universal platform developed, and perioperative application scenarios explored. NK vaccines, by reshaping the immune microenvironment, will be an attractive strategy to break the bottlenecks in the treatment of solid tumors.